Partners. - Gooding, Mel (London : Annely Juda Fine Art, 1993)
Arp, Hans (Jean) ; Bergmann-Michel, Ella ; Caro, Anthony ; Cohen, Nathan ; Delaunay, Robert ; Delaunay, Sonia ; Girling, Sheila ; Gontcharova, Natalia ; Green, Alan ; Green, June ; Hall, Nigel ; Hausmann, Raoul ; Hepworth, Barbara ; Höch, Hannah ; Kobro, Katarzyna ; Krasner, Lee ; Kubota, Reiko ; Larionov, Michail ; Lee, Catherine ; Martin, Kenneth ; Martin, Mary ; Michel, Robert ; Nicholson, Ben ; Pollock, Jackson ; Popova, Liubov ; Rodchenko, Alexander ; Scully, Sean ; Stepanova, Varvara ; Strzeminski, Wladyslaw ; Taeuber-Arp, Sophie ; Vesnin, Alexandr ; Yadegar, Manijeh
biog. per kunstenaar
Engels
Partners, Annely Juda Fine Art, London, 24 June - 18 September 1993
boek